Smart Automation for Enhancing Cybersecurity - Ângelo Neves; Virgínia M. Araújo (Foresight and STI Governance)
In an intelligent automation ecosystem, namely in the context of Robotic Process Automation, there is a need to review the development and operation processes and practices. One must combine competences from these two areas necessary for any organization’s security. It is with security that quality, efficiency, and profitability become possible.The elaboration of guidelines and best practices for the application of a DevSecOps culture is absolutely essential for Agile software development at any organization. In the digitalization era, teams increasingly need a collaborative method to involve several competencies and capabilities, from analysis to the implementation and evolution of a software product. Information security must be an integral part throughout the entire product’s lifecycle, as without it, fundamental aspects of confidentiality, integrity, and availability put information and software security at risk of serious implications for the organization’s business activities.Without losing focus on customer needs, it is necessary to model software development practices, following more agile methodologies. In this way, teams can model the software throughout its lifecycle, focusing on adding value for the customer and ensuring they have greater certainty that requirements, plans, and results are 100% aligned with their needs.This paper presents an analysis of and proposal for the continuous improvement of an intelligent automation platform at a large-scale multinational organization. In parallel, aspects that generate resistance to the implementation of a DevSecOps methodology within the scope of RPA code development are considered.